Construction of pediatric homogeneous phantoms for optimization of chest and skull radiographs - Alves, Allan Felipe Fattori [UNESP]; Miranda, José Ricardo de Arruda[UNESP]; Bacchim Neto, Fernando Antonio [UNESP]; Duarte, Sergio Barbosa; Pina, Diana Rodrigues de [UNESP] (Elsevier B.V., 2015)
Objectives: To develop two pediatric patient-equivalent phantoms, the Pediatric Chest Equivalent Patient (PCEP) and the Pediatric Skull Equivalent Patient (PSEP) for children aged Ito 5 years. We also used both phantoms for image quality evaluations in computed radiography systems to determine Gold Standard (GS) techniques for pediatric patients.Methods: To determine the simulator materials thickness (Lucite and aluminum), we quantified biological tissues (lung, soft, and bone) using an automatic computational algorithm. To objectively establish image quality levels, two physical quantities were used: effective detective quantum efficiency and contrastto-noise ratio. These quantities were associated to values obtained for standard patients from previous studies.Results: For chest radiographies, the GS technique applied was 81 kVp, associated to 2.0 mAs and 83.6 tiGy of entrance skin dose (ESD), while for skull radiographies, the GS technique was 70 kVp, associated to 5 mAs and 339 tiGy of ESD.Conclusion: This procedure allowed us to choose optimized techniques for pediatric protocols, thus improving quality of diagnosis for pediatric population and reducing diagnostic costs to our institution. These results could also be easily applied to other services with different equipment technologies. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: Chest and skull; Pediatric homogenous phantom; Image quality; Dose optimization